Inovasi Skema Musyarakah Mutanaqisah Untuk Pembiayaan Aset Produktif Umkm Di Sektor Kreatif - Iwan Mulyana; Rahmat (Integrative Perspectives of Social and Science Journal, 2025)
Kata kunci: Musyarakah Mutanaqisah, UMKM, Sektor Kreatif, Aset Produktif, Pembiayaan Syariah, Bank Syariah   Abstract: The creative economy sector has become one of the important pillars in Indonesia's economy, but SMEs in this sector still face constraints in accessing financing for productive assets. This research aims to analyze the innovation of the Musyarakah Mutanaqisah scheme as a financing solution for productive assets for SMEs in the creative sector. The research method uses a qualitative approach with descriptive analysis of the Musyarakah Mutanaqisah concept and its implementation in creative SMEs. The research results show that the Musyarakah Mutanaqisah scheme can be innovated through the use of intellectual property rights as collateral, flexible multi-contract structures, and fair profit-sharing mechanisms. This innovation provides easier access to financing for creative SMEs to obtain productive assets such as equipment, technology, and commercial property. The research conclusion shows that the innovation of the Musyarakah Mutanaqisah scheme can be an effective solution to increase financing access for creative sector SMEs to productive assets.   Keywords: Musyarakah Mutanaqisah, SMEs, Creative Sector, Productive Assets, Islamic Financing, Islamic Bank